Lipophilic dispersed phenolic polymer particles

By applying surfactants on phenolic polymer particles, lipophilic phenolic polymer particles are formed, which solves the problem of using the solid state caused by the high water solubility of phenolic polymers, and achieves its stable existence and efficient antioxidant properties in the oil phase.

CN114727939BActive Publication Date: 2025-04-08NANOPHASE TECHNOLOGIES CORP
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
CN202080075151.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-13
Filing Date
2020-09-08
Publication Date
2025-04-08
Estimated Expiration
2040-09-08

AI Technical Summary

Technical Problem

Due to its high water solubility, phenol polymers are difficult to include in topical formulations in solid form, limiting their use time on the skin.

Method used

By applying a surfactant on the phenolic polymer particles, lipophilic phenolic polymer particles are formed so that they can exist in the oil phase, thereby expanding their use.

Benefits of technology

It realizes that the phenolic polymers are stable in the preparation in solid form, improves their water resistance and light stability, enhances antioxidant properties, and is suitable for sun protection and skin care products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114727939B_ABST
    Figure CN114727939B_ABST
Patent Text Reader

Abstract

The composition comprises phenolic polymer particles and a surfactant on the phenolic polymer particles. The composition is lipophilic. The dispersion comprises phenolic polymer particles, a surfactant and a carrier medium. The carrier medium can be a cosmetically acceptable fluid or a lipophilic wax.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] Phenolic polymers are a class of organic polymers characterized by the presence of multiple OH-substituted phenyl groups. Phenolic polymers have many unique properties, such as the ability to act as antioxidants or skin conditioning agents. These properties have led to the inclusion of phenolic polymers in topically applied formulations, such as cosmetic and dermatological preparations. Well-known examples of phenolic polymers include lignin, lignin sulfonates, humates, and tannins.

[0002] Lignin is a particularly desirable phenolic polymer because it is ubiquitous. Modern papermaking processes involve the removal of lignin from wood cellulose. The global paper industry produces approximately 40–50 million tons of lignin per year as a waste product (The International Lignin Institute, “About lignin,” available online at www.ili-lignin.com / aboutlignin.php (accessed Aug. 30, 2019)). Lignin is also produced as a byproduct of sulfite pulping to remove lignin from wood pulp. Waste lignin is often burned to provide energy for the paper mills that produced it. Methods have been developed to convert waste lignin sulfonate and kraft lignin into useful commodities. For example, waste lignin can be obtained from using TECHNOFORCE TM High-quality lignin is obtained from the black liquor produced in the Kraft process of papermaking. However, tens of millions of tons of waste lignin are still produced every year, which can be converted into useful chemical products.

[0003] Despite their usefulness as raw materials, formulation challenges have limited demand for phenolic polymers. Lignin and other phenolic polymers are very soluble in water. Therefore, phenolic polymers are only included in the aqueous phase of a formulation. The high water solubility of phenolic polymers also limits their inclusion in topical formulations in solid form, as the phenolic polymers will wash off the user's skin if exposed to water. These solubility issues limit the ability of manufacturers to fully exploit the useful properties of phenolic polymers. Summary of the invention

[0004] In a first aspect, the present invention provides a composition comprising phenolic polymer particles and a surfactant on the phenolic polymer particles.

[0005] In a second aspect, the present invention provides a dispersion comprising sodium lignin sulfonate particles, a surfactant and a carrier medium. The particle size of the sodium lignin sulfonate particles is 0.1-1.0 microns. The dispersion is pourable.

[0006] In a third aspect, the present invention provides a dispersion comprising silanized phenolic polymer particles and a carrier medium.

[0007] In a fourth aspect, the present invention provides a lipophilic phenolic polymer particle.

[0008] definition

[0009] The term "phenolic polymer" refers to a water-soluble polymer comprising a plurality of OH-substituted phenyl groups. Examples of phenolic polymers include lignin, humates, tannins, and plant extracts containing water-soluble and / or water-dispersible components.

[0010] The term "ultraviolet radiation" refers to electromagnetic radiation having a wavelength of 10-400 nm. Ultraviolet radiation is also known as ultraviolet light, UV radiation or UV light. In this application, the abbreviation "UV" is used interchangeably with the phrase "ultraviolet light".

[0011] The term "high-energy visible radiation" or "HEV radiation" refers to electromagnetic radiation with a wavelength of 400–490 nm. HEV radiation is seen as blue and violet light in the visible spectrum.

[0012] Unless otherwise stated, the term "particle size" refers to the median (D50) particle size determined by static light scattering based on number distribution (ISO 13320:2009 Particle size analysis - laser diffraction method).

[0013] The term "very water resistant" refers to a composition whose MPF changes less than 50% between its monochromatic photoprotection index (MPF) before exposure to water and its MPF after 80 minutes of in vitro immersion in water (Cosmetics Europe, "Guidelines for evaluating sun product water resistance", available online at www.cosmeticseurope.eu / files / 7914 / 6407 / 7400 / Guidelines_for_Evaluating_Sun_Product_Water_Resistance_-_2005.pdf, page 15 (2005)).

[0014] The "Modified DPPH Photostability Test" is a method to measure the photostability of active materials. The Modified DPPH Photostability Test is a more sensitive test than the DPPH Photostability Test described in U.S. Patent Application Publication No. 2018 / 0291210 and has been validated for compositions other than zinc oxide. First, 0.025 g ± 0.001 g of active material was added to four 50 mL disposable plastic beakers. 0.0125% DPPH (di(phenyl)-(2,4,6-trinitrophenyl) iminohydrazine, also known as diphenylpicrylhydrazyl; CAS No. 1898-66-4) was prepared in BCS (ethylene glycol butyl ether) solution. 19.975 g ± 0.001 of the 0.0125% DPPH solution in BCS was added to each beaker containing the active material to form a test mixture. The test mixture was stirred thoroughly with a glass stirring rod, and each test mixture was sonicated for 20 seconds to ensure that the active material was fully dispersed. After sonication, each test mixture was transferred to a labeled scintillation vial. The absorbance of the test mixture was measured on a calibrated colorimeter to obtain pre-irradiation measurements. After the measurement was made, the irradiation was performed in a Q-Labs QUVWeatherometer using a 0.35 Wm -2 s -1 The test mixture was exposed to UV light at a constant temperature of 50°C for 10 minutes using a UVA bulb. After irradiation, the absorbance of the test mixture was measured on a colorimeter. The photostability after exposure to UV was determined by the persistence of the purple color produced by the dye's absorption band at 520 nm.

[0015] Light stability can be expressed as the total color change relative to a standard (ΔE in L*a*b* color space) for a specified UV exposure time. According to the definition of the International Commission on Illumination standard CIE76, ΔE is calculated by the following equation 1:

[0016] Equation 1: Where L * 2.a * 2 and b * 2 is the color coordinate of the test mixture after irradiation, L * 1.a * 1 and b * 1 is the color coordinate of the test mixture before irradiation. The data are reported as the average ΔE value of four samples.

[0017] The term "superphotostable" refers to a substance having a ΔE ≤ 4.5 when tested using the modified DPPH photostability test.

[0018] The “free radical quenching test” is a method to measure the ability of active materials to quench free radicals. First, the photostability of titanium dioxide (35 nm, rutile phase) was measured according to the modified DPPH photostability test to establish a reference photostability (ΔE Ref ). Next, a test mixture containing the same weight percentage of titanium dioxide and the same amount of active material for establishing the reference photostability was prepared. The photostability of the test mixture was then measured according to the modified DPPH photostability test to establish the test photostability (ΔE Test Then, the reference photostability (ΔE Ref ) and tested photostability (ΔE Test ) to determine the free radical quenching ability of the active material. If the active material can quench at least 70% of the free radicals generated by titanium dioxide (ΔE Test At least ΔE Ref If the active material has a free radical quenching test, the free radical quenching test is passed.

[0019] Unless otherwise stated, all percentages (%) are weight / weight percentages. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The invention may be better understood with reference to the following drawings and description.

[0021] FIG1 is a cartoon representation of phenolic polymer particles modified with surfactants. DETAILED DESCRIPTION

[0022] The present invention includes phenolic polymer particles that have been modified to be lipophilic. The lipophilic phenolic polymer particles can be formed by adding surface treatments to the particles or by reacting the particles with a silanizing agent. The lipophilic modification enables the phenolic polymer to be present in the oil phase of the formulation in a solid state. For example, the phenolic polymer particles and a surfactant can be dispersed in a lipophilic carrier medium. The ability to use the phenolic polymer particles in the oil phase greatly expands the possible uses of these particles.

[0023] Experimental testing showed that formulations including lipophilic phenolic polymer particles possess a number of desirable physical and chemical properties. These formulations are very water resistant and are strong HEV light blockers, suggesting that they are well suited for use in sunscreen formulations. The formulations are also super photostable when subjected to a modified DPPH photostability test. In addition, the formulations passed a free radical quenching test, illustrating their strong antioxidant properties.

[0024] Without wishing to be bound by theory, it is believed that these properties result from the presence of the phenolic polymer in the solid state. Physical interactions between the phenolic polymer molecules result in pi (π) stacking of the aromatic groups, thereby increasing the ability of these molecules to accept electrons due to orbital mixing. Although pi stacking can occur when the phenolic polymer is in solution, the solution must have a sufficiently high concentration. Delivering the phenolic polymer as particles (i.e., in the solid state) ensures that they have pi stacking.

[0025] Formulations containing phenolic polymer particles also have many commercial advantages. Phenolic polymers, especially lignin, are economically advantageous raw materials because they are available in large quantities as waste. Capturing waste that would otherwise be burned is an environmentally friendly process because it prevents carbon emissions. Phenolic polymers derived from natural sources can be sold as natural products, which is particularly attractive to consumers. In addition, dispersions of phenolic polymer particles can be prepared using conventional chemical processing techniques that do not require expensive reactants, extreme temperatures, long reaction times or hazardous reactants and do not produce hazardous waste. All of these advantages will encourage manufacturers to include phenolic polymers in commercial formulations.

[0026] FIG1 shows a cartoon representation of phenolic polymer particles modified with surfactants. Composition 100 comprises phenolic polymer particles 110 and surfactant 120 on the surface of the particles. Surfactant is a surface treatment agent that makes the phenolic polymer particles lipophilic and insoluble in water. A dispersion can be prepared by mixing the phenolic polymer particles, surfactant and carrier medium. Preferably, the dispersion is pourable.

[0027] The phenolic polymer particles can be any polymer with a plurality of OH-substituted phenyl groups. Preferably, the phenolic polymer particles are lignin, humates, tannins, plant extracts containing water-soluble and / or water-dispersible components, or a combination thereof. The example of suitable lignin comprises lignin sulfonate, kraft lignin, sulfonated kraft lignin, oxidized lignin, sulfonated oxidized lignin, lignin sulfonate copolymerized with monomers (such as acrylate, acrylic acid, acrylamide, styrene sulfonate and naphthalene sulfonate derivatives), azosulfonates, azolignin, lignin sulfonate-formaldehyde condensates, lignin formaldehyde condensates, hydrophobically modified lignin sulfonate, hydrophobically modified lignin, cationically modified lignin sulfonate, cationically modified lignin, amino lignin sulfonate, amino lignin, alkylated lignin sulfonate, alkylated lignin, cross-linked lignin sulfonate and cross-linked lignin. Examples of suitable humates include sulfonated humates, humate-formaldehyde condensates, hydrophobically modified humates, cationically modified humates, aminohumates, and alkylated humates. Examples of suitable tannates include tannates, sulfonated tannates, tannate-formaldehyde condensates, hydrophobically modified tannates, and cationically modified tannates.

[0028] Examples of plant extracts containing water-soluble and / or water-dispersible components include extracts derived from plants known as Acacia, Afzelia, Synsepalum duloificum, Albizia, alder (e.g., Alnus glutinosa and Alnus rubra), applewood, Arbutus, ash (e.g., F. nigra, F. quadrangulata, F. excelsior, F. pennsylvanica lanceolata, F. latifolia, F. profinda, and F. americana), poplar (e.g., P. grandidentata, P. tremula, and P. tremloides), Australian red cedar (Toona ciliata), ayan (Distemonanthus benthamianus), balsa (Ochromapyramidale), basswood (e.g. T. Americana and T. heterophylla), beech (e.g. F. Sylvatica and F. grandifolia), birch (e.g. Betula populifolia, river birch (B. nigra), paper birch (B. papyrifera), sweet birch (B. lenta), B. allegha niensis, yellow birch (B.lutea), weeping birch (B.pendula), and B.pubescens), black bean, blackwood, bocote, boxelder, boxwood, brazilwood, bubinga, buckeye (e.g., Aesculushippocastianum, Aesculusglabra, and Aesculusflava / Aesculusoctandra), butternut, catalpa, cherry (e.g., Prunus serotina, Prunuspennsylvanica, and Prunusavium), crabwood, chestnut, coachwood, cocobolo, corkwood, cottonwood (e.g., Populus balsamifera, Populus deltoides, Populus sargentii, and Populus heterophylla), cucumber tree, dogwood (e.g., Cornus florida and Cornus nuttallii), ebony (e.g., Diospyros kurzii, Diospyros melanida, and Diospyros crassiflora), elm (e.g., Ulmus americana, Ulmus procera, Ulmus thomasii, Ulmus rubra and Ulmus glabra), eucalyptus, greenheart, grenadilla, gum (e.g., Nyssa sylvatica, Eucalyptus globulus, Liquidambarstyraciflua, and Nyssa aquatica), hickory (e.g., Carya alba, Carya glabra, Carva ovata, and Carya laciniosa), hornbeam, hophornbeam, ipe, iroko, ironwood (e.g., Bangkirai, Carpinus caroliniana, Casuarina equisetifolia, Choricbangarpia subargentea, Copaifera spp., Eusideroxylon zwageri, Guaiacum officinale, Guaiacum sanctum, Hopea odorata, Krugiodendronferreum, Lyonothamnus ivonii (L.floribundus), Mesuaferrea, Oleaspp., Olneya tesota, Ostryavirginiana, Parrotiapersica, and Tabebuia serratifolia), jacaranda, jojoba, lacewood, laurel, limba, Lignum vitae, locust (e.g., Robiniapseudacacia and Gleditsiatriacanthos), mahogany, maple (e.g., Acersaccharum, Acer nigrum, Acer negundo, Acer rubrum), silver maple (Acer Saccharinum) and Eurasian maple (Acer pseudoplatanus), meranti, mpingo, oak (such as Quercus macrocarpa, Quercus alba, Quercus stellata, Quercus bicolor, Quercus virginiana, Quercus michauxii, Quercus prinus, Quercus muhlenbergii, Quercus chrysolepis, Quercus lyrata, Quercus robur, Quercus petraea, Quercus rubra, Quercus velutina, Quercus laurifolia, Quercus falcata, Quercus nigra), willow oak (Quercus phellos) and Texas oak (Quercus texana), obeche, okoumé, Oregon myrtle, California bay laurel, pearwood, poplar (such as balsam poplar (P. balsamifera), European black poplar (P. nigra) and hybrid poplar (Populus Xcanadensis), ramin, red cedar (cedar, rosewood, sal, sandalwood, sassafras, satinwood, silky oak, silverwattle, snakewood, sourwood, Spanish cedar, American sycamore, teak, walnut (e.g., Juglans nigra and Juglans regia), willow (e.g., Salix nigra and Salix alba), yellow poplar (Liriodendron tulipifera), Araucaria (e.g., A. cunninghamii, A. angustifolia, and A. araucana), softwood cedar (e.g., Juniperus virginianus), virginiana), Thujaplicata, Thuja occidentalis, Chamaecyparis thyoides and Callitropsisnootkatensis, cypress (e.g., Chamaecyparis, Cupressus taxodium, Cupressus arizonica, Taxodium distichum, Chamaecyparis isobtusa, Chamaecyparis lawsoniana, and Cupressus semperviren), Rocky Mountain Douglas fir, European yew, fir (e.g., Abies balsamea, Abies alba, Abies procera, and Abies amabilis), hemlock (e.g., Tsuga canadensis), Canadensis, Tsugamertensiana, and Tsugaheterophylla), kauri, kaya, larch (e.g., Larix decidua, Larix kaempferi, Larix laricina, Larix occidentalis, and Larix europea), pine (e.g., Pinus nigra, Pinus banksiana, Pinus contorta, Pinus radiata, Pinus ponderosa, Pinus resinosa, Pinus sylvestris, Pinus strobus, Pinus monticola, Pinus lambertiana, Pinus taeda, Pinus palustris, Pinus truncatula ... rigida and bud pine (Pinus echinata), redwood, rimu, spruce (e.g., Picea abies, Picea mariana, Picea rubens, Picea sitchensis and Picea aglauca), sugi and mixtures / hybrids thereof. Preferred plant extracts containing water-soluble and / or water-dispersible components include those derived from spruce (also known as Norway spruce or European spruce), Larix europaea (also known as larch or European larch) and maple species (a mixture of sugar maple, silver maple and ash maple).

[0029] The surfactant may be any surfactant that has a strong acid-base interaction with the phenolic polymer particles and provides a lipophilic surface treatment on the particles. Examples of suitable surfactants include fatty alcohols and polyols (e.g., stearyl alcohol, behenyl alcohol, and cetearyl alcohol), fatty acids (e.g., stearic acid and oleic acid), amino acids (e.g., lauroyl lysine and myristoyl glutamate), polyglyceryl esters (e.g., polyglyceryl-3 ricinoleate, polyglyceryl-6 ricinoleate, polyglyceryl-10 pentastearate, and polyglyceryl-4 oleate), polyglyceryl polyesters (e.g., polyglyceryl-4 diisostearate / polyhydroxystearate / sebacate, polyglyceryl-2 dipolyhydroxystearate, and polyglyceryl-3 stearate / isostearate / dimer linoleate crosspolymers), hydroxyl-affinic acid (affinic acid) and hydroxyl-affinic acid (affinic acid). hydroxyl), amine or amide polyesters (such as polyhydroxystearic acid), polyurethanes having affinity for hydroxyl, amine or amide groups, polyamides having affinity for hydroxyl, amine or amide groups, polyacrylates having affinity for hydroxyl, amine or amide groups, phosphates (such as tris(laureth-4) phosphate and tris(ceteareth-4) phosphate), polymeric phosphates (such as 1,2-ethylenediamine, polymers with aziridine, N-[3-[(2-ethylhexyl)oxy]-3-oxypropyl] derivatives and compounds including polyethylene-polypropylene glycol), phospholipids, ceramides, sphingosides (such as lecithin, lysolecithin and ceramide 3), substituted silicones having affinity groups (such as cetyldiglyceryl tris(trimethylsiloxy)silylethyl polydimethylsiloxane dimethicone), CAS No. 104780-66-7 (Siloxanes and Silicones, Dimethyl, 3-Hydroxypropyl Terminated), CAS No. 102782-61-6 (Siloxanes and Silicones, Dimethyl, 3-Hydroxypropyl Methyl) and CAS No. 106214-84-0 (Siloxanes and Silicones, Dimethyl, 3-Aminopropyl)) and combinations thereof.

[0030] Alternatively, lipophilic phenolic polymer particles can be formed by reacting the particles with a silanizing agent. The silanizing agent can be any substance that provides functionalized polysiloxane on the surface of the phenolic polymer particles. Examples of suitable silanizing agents include reactive siloxanes and silane hydrophobic surface treatment agents (e.g., triethoxyoctylsilane, octadecyltriethoxysilane, hydrogendimethylsiloxane (CAS No. 68037-59-2 / 69013-23-6 / 70900-21-9) and CAS No. 69430-47-3 (siloxane and silicone resin, dimethyl, methylhydrogensiloxane and 1,1,3,3-tetramethyldisiloxane reaction product)).

[0031] The carrier medium can be any cosmetically acceptable lipophilic fluid or wax. Examples of suitable carrier media include triglycerides (e.g., caprylic / capric triglycerides), esters (e.g., C12-C15 alkyl benzoates, isoamyl laurate, isopropyl isostearate, coco-caprylate, ethylhexyl isononanoate, tridecyl salicylate, ethylhexyl isononanoate, isodecyl salicylate, octyldodecyl neopentanoate, butyloctyl salicylate, jojoba esters, and shea butter ethyl esters), natural oils and butters (e.g., jojoba seed oil (Simmondsia chinensis (jojoba) seed oil), shea butter, argan oil (Argania spinosa (Argan) oil), pongami (karanja) oil, and Limnanthes alba (white meadowfoam) seed oil (Limnanthes alba (white meadowfoam) seed oil). oil), alkanes (e.g., squalane, hemi-squalane, isododecane, and isohexadecane), silicones (e.g., dimethicone, behenyl dimethicone, cetyl dimethicone, cetearyl methicone, and phenyl dimethicone), waxes (e.g., natural waxes, synthetic waxes, and silicone waxes), and combinations thereof.

[0032] The amount of phenolic polymer particles in the dispersion may be 0.1-75.0 wt%, including 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1.0 wt%, 2.0 wt%, 3.0 wt%, 4.0 wt%, 5.0 wt%, 6.0 wt%, 7.0 wt%, 8.0 wt%, 9.0 wt%, 10.0 wt%, 15.0 wt%, 20.0 wt%, 25.0 wt%, 30.0 wt%, 35.0 wt%, 40.0 wt%, 45.0 wt%, 50.0 wt%, 55.0 wt%, 60.0 wt%, 65.0 wt%, and 70.0 wt%. Preferably, the amount of phenolic polymer particles is 0.5-50.0 wt%. More preferably, the amount of phenolic polymer particles is 1.0 - 40.0 wt%.

[0033] The amount of surfactant in the dispersion can be 1.0-100.0% by mass of the phenolic polymer particles, including 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, 10.0%, 11.0%, 12.0%, 13.0%, 14.0%, 15.0%, 16.0%, 17.0%, 18.0%, 19.0%, 20.0%, 21.0%, 22.0%, 23.0%, 24.0%, 25 %, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, 15.0%, 20.0%, 25.0%, 30.0%, 35.0%, 40.0%, 45.0%, 50.0%, 55.0%, 60.0%, 65.0%, 70.0%, 75.0%, 80.0%, 85.0%, 90.0% and 95.0%. Preferably, the amount of surfactant is 10.0-60.0% by mass of the phenolic polymer particles. More preferably, the amount of surfactant is 20.0-50.0% by mass of the phenolic polymer particles.

[0034] The amount of carrier medium in the dispersion depends on the amount of phenolic polymer particles and the amount of surfactant in the dispersion.After mixing the phenolic polymer particles and surfactant, the carrier medium may be added in any suitable amount required to produce the desired dispersion.

[0035] Dispersion can be prepared by conventional formulation techniques. For example, phenolic polymer particles, surfactants and carrier media can be mixed and stirred in a container until uniform. Appropriate mixing conditions, such as temperature, stirring speed and mixing time, can be changed to obtain the desired dispersion. The dispersion can then be transferred to a grinder (e.g., a media grinder) and pulverized to obtain the desired particle size.

[0036] The phenolic polymer particles may have a particle size of 0.001–10.0 micrometers (μm) (1–10,000 nm), including 0.002 μm, 0.003 μm, 0.004 μm, 0.005 μm, 0.006 μm, 0.007 μm, 0.008 μm, 0.009 μm, 0.01 μm, 0.02 μm, 0.03 μm, 0.04 μm, 0.05 μm, 0.06 μm, 0.07 μm, 0.08 μm, 0.09 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 0.10 μm, 0.11 μm, 0.12 μm, 0.13 μm, 0.14 μm, 0.15 μm, 0.16 μm, 0.17 μm, 0.18 μm, 0.19 μm, 0.20 μm, 0.21 μm, 0.22 μm, 0.23 μm, 0.24 μm, 0.25 μm, 0.26 μm, 0.27 μm, 0.28 μm, 0.29 μm, 0.30 μm, 0.31 μm, 0.32 μm, 0.33 μm, 0.34 μm, 0.35 μm, 0.36 μm, 0.37 μm, 0.38 μm, 0.39 μm, 0.39 μm, 0.31 μm, 0.39 μ um, 10-15 μm, 10-20 μm, 10-30 μm, 10-40 μm, 10-50 μm, 10-60 μm, 10-80 μm, 10-90 μm, 10-15 μm, 10-20 μm, 10-30 μm, 10-40 μm, 10-50 μm, 10-60 μm, 10-80 μm, 10-90 μm, 10-15 μm, 10-15 μm, 10-20 μm, 10-30 μm, 10-40 μm, 10-50 μm, 10-60 μm, 10-15 μm, 10-20 μm, 10-30 μm, 10-40 μm, 10-50 μm, 10-60 μm, 10-15 μm More preferably, the phenolic polymer has a particle size of 0.1-1.0 μm (100-1,000 nm). The maximum particle size of the phenolic polymer particles is 10.0 μm to prevent the particles from being felt on the skin and to avoid a formulation that has a gritty or grainy texture to the user.

[0037] The lipophilic phenolic polymer particles can be obtained from a dispersion of phenolic polymer particles, a surfactant and a carrier medium by removing the carrier medium. For example, the carrier medium can be a volatile substance that evaporates at ambient temperature and pressure. Similarly, the dispersion can be heated to above the boiling point of the carrier medium until the carrier medium is removed.

[0038] Lipophilic phenolic polymer particles can also be prepared directly without being prepared by separation from a dispersion. First, the particle size of the phenolic polymer particles is reduced by dry pulverization. Any suitable dry pulverization technology can be used, such as high performance air grinding, vibration grinding, media grinding, hammer milling and jet grinding. Pulverization can be carried out alone or with auxiliary materials such as polymer particles or oxides (such as metal oxides and silicates (such as mica or silicon dioxide)). Next, a solution is prepared by dissolving a surfactant or silanizing agent in a suitable solvent. Examples of suitable solvents include USP heptane, USP acetone, USP isopropanol and USP ethanol. Then, the solution is sprayed onto the pulverized phenolic polymer particles under stirring in an agitator / mixer. The solution and the pulverized phenolic polymer particles can be optionally heated to promote the reaction of bonding a surfactant or silanizing agent to the particles. Finally, a vacuum is applied to remove the solvent.

[0039] The lipophilic phenolic polymer particles can be present in the oil phase of the preparation, or can be added to the powder preparation. Preferably, the preparation is suitable for topical application. Examples of suitable preparations include emulsions (oil-in-water emulsions and water-in-oil emulsions), sprays, balms, sticks, powders, powder-to-cream preparations, lipophilic preparations and anhydrous preparations. Preparations comprising lipophilic phenolic polymer particles can be evaluated by one or more tests. Preferably, preparations comprising lipophilic phenolic polymer particles are very water-resistant, super light-stable and have passed free radical quenching tests.

[0040] Formulations containing lipophilic phenolic polymer particles can be formulated for a variety of uses. Examples of suitable formulations include cosmetics (e.g., blush, pressed powder, foundation, lipstick, base makeup, and rouge), skin care products (e.g., skin cleansing creams, lotions, liquids, and pads; face and neck creams, lotions, powders, and sprays; body and hand creams, lotions, powders, and sprays; foot powders and sprays; moisturizers; night creams, lotions, powders, and sprays; paste masks / mud packs; and skin fresheners) and sunscreens. Sunscreens are particularly preferred formulations. The formulations can be provided in any form suitable for topical application, such as in the form of topical suspensions, lotions, creams, ointments, gels, hydrogels, foams, pastes, tinctures, liniments, sprayable liquids, aerosols, sticks, or powders. The formulations may optionally include inactive ingredients, adjuvants and / or additives (e.g., co-emulsifiers, fats, waxes, stabilizers, thickeners, biologically active ingredients, film formers, fragrances, dyes, pearlescent agents, preservatives, pigments, electrolytes and pH adjusters).

[0041] Sunscreens may include lipophilic phenolic polymer particles and UV radiation protectants. UV radiation protectants may be any substance that absorbs, reflects and / or scatters UV radiation. Sunscreens may optionally include sun protection factor (SPF) enhancers or stabilizers, such as methoxypropylene and polyester-8.

[0042] Examples of suitable UV radiation protectants include zinc oxide (ZnO), titanium dioxide (TiO2), p-aminobenzoic acid (PABA), isooctyl-p-dimethylaminobenzoate (padimate O) (OD-PABA, octyldimethyl-PABA, σ-PABA), phenylbenzimidazole sulfonic acid (ensulizole, 232, PBSA, HS), cinoxate (2-ethoxyethyl p-methoxycinnamate), dioxybenzone (benzophenone-8), oxybenzone (benzophenone-3, 4360, 567), homosalate (homomethylsalicylate, HMS), menthyl anthranilate (menthyl anthranilate (meradimate)), octocrylene ( OCR, 2-cyano-3,3-diphenylacrylate, 2-ethylhexyl ester), octyl methoxycinnamate (octinoxate, EMC, OMC, ethylhexyl methoxycinnamate, 557, 2-methoxycinnamic acid ethylhexyl ester, MCX), octisalate, 2-ethylhexyl salicylate, 587), sulisobenzone (2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, 3-benzoyl-4-hydroxy-6-methoxybenzenesulfonic acid, benzophenone-4, 577), triethanolamine salicylate (triethanolamine salicylate), avobenzone (1-(4-methoxyphenyl)-3-(4-tert-butylphenyl) propane-1,3-dione, butyl methoxydibenzoylmethane, BMDBM, 1789, 9020), ecamsule ( SX, terephthaloyl dicamphor sulfonic acid), cerium oxide (CeO2), domethoxazole trisiloxane ( XL), bis-ethylhexyloxyphenol methoxyphenyl triazine ( S), bis-triazole ( M.MILESTAB TM 360) and combinations thereof. Preferred UV radiation protectants include zinc oxide (ZnO), titanium dioxide (TiO2) and combinations thereof. Preferably, the UV radiation protectant has been approved by at least one regulatory agency of the United States (Food and Drug Administration or FDA), Canada, the European Union, Australia, Japan, South Korea, China, Mercosur, the Association of Southeast Asian Nations (ASEAN), the Commonwealth of Independent States (CIS) and the Gulf Cooperation Council (GCC).

[0043] Sunscreens containing lipophilic phenolic polymer particles have many advantages over conventional sunscreens. The addition of phenolic polymer particles produces a very water-resistant sunscreen. In addition, phenolic polymer particles allow sunscreens to block or attenuate UV radiation and HEV radiation. Phenolic polymer particles can also resist photoinduced free radicals generated by UV radiation and HEV radiation.

[0044] Preparations comprising lipophilic phenolic polymer particles can provide multiple health benefits. Phenolic polymer particles are used as antioxidants because they are very effective in neutralizing free radicals. These characteristics enable phenolic polymer particles to treat or prevent oxidative stress or damage to skin, hair and nails. For example, phenolic polymer particles can be used to protect keratinous materials (such as hair, fingernails, toenails and skin outer layer), protect human skin, inhibit lipid peroxidation, prevent or reduce fine lines and wrinkles on the skin, prevent skin from losing elasticity, prevent skin from thinning, and prevent skin pigmentation. These health benefits can be obtained by applying the preparation containing lipophilic phenolic polymer particles to the skin area.

[0045] Example

[0046] Example 1 - Dispersion of Sodium Lignosulfonate and Polyglyceryl-2 Dipolyhydroxystearate in Caprylic / Capric Triglyceride

[0047] 30.0 parts by weight of sodium lignin sulfonate (VanisperseA, Borregaard LignoTech) was mixed with 10.5 parts by weight of polyglycerol-2 dipolyhydroxystearate and 59.5 parts by weight of caprylic / capric triglyceride. The mixture was stirred until uniform, transferred to a horizontal media mill, and pulverized using 0.3 mm yttria-stabilized zirconium oxide media until the maximum particle size was less than 0.5 microns, as shown on a Hegman gauge with a 0.5 scale grade indicated at 0–12 microns. The resulting dispersion was pourable. The particle size of the sodium lignin sulfonate particles in the dispersion was measured to be 0.169 microns by static light scattering, and no particles below 0.1 microns were detected.

[0048] Example 2 - Dispersion of Sodium Lignosulfonate and Polyglyceryl-2 Dipolyhydroxystearate in Coco-Caprylate

[0049] 30.0 parts by weight of sodium lignin sulfonate (Vanisperse A, Borregaard LignoTech) was mixed with 13.5 parts by weight of polyglyceryl-2 dipolyhydroxystearate and 56.5 parts by weight of coco-caprylate. The mixture was stirred until homogeneous, transferred to a horizontal media mill, and pulverized using 0.3 mm yttria-stabilized zirconium oxide media until the maximum particle size was less than 0.5 microns, as indicated on a Hegman gauge with a 0.5 scale grade indicating 0-12 microns. The resulting dispersion was pourable.

[0050] Example 3 - Dispersion of Sodium Lignosulfonate and Polyhydroxystearic Acid in Coco-Caprylate

[0051] 30.0 parts by weight of sodium lignin sulfonate (Vanisperse A, Borregaard LignoTech) was mixed with 12.0 parts by weight of polyhydroxystearic acid and 58.0 parts by weight of coco-caprylate. The mixture was stirred until homogeneous, transferred to a horizontal media mill, and crushed using 0.3 mm yttria-stabilized zirconium oxide media until the maximum particle size was less than 0.5 microns, as shown on a Hegman gauge with a 0.5 scale grade indicating 0-12 microns. The resulting dispersion was pourable.

[0052] Example 4 - Dispersion of Sodium Lignosulfonate and Lecithin in Caprylic / Capric Triglyceride

[0053] 30.0 parts by weight of sodium lignin sulfonate (Vanisperse A, Borregaard LignoTech) was mixed with 14.0 parts by weight of lecithin and 56.0 parts by weight of caprylic / capric triglyceride. The mixture was stirred until homogeneous, transferred to a horizontal media mill, and pulverized using 0.3 mm yttria-stabilized zirconium oxide media until the maximum particle size was less than 0.5 microns, as indicated on a Hegman gauge with a 0.5 scale grade indicated at 0–12 microns. The resulting dispersion was pourable.

[0054] Example 5 - Dispersion of Sodium Lignosulfonate and Polyglyceryl-2 Dipolyhydroxystearate in C12-C15 Alkyl Benzoate

[0055] 30.0 parts by weight of sodium lignin sulfonate (Maracell XE, Borregaard LignoTech) was mixed with 13.5 parts by weight of polyglyceryl-2 dipolyhydroxystearate and 56.5 parts by weight of C12-C15 alkyl benzoate. The mixture was stirred until homogeneous, transferred to a horizontal media mill, and pulverized using 0.3 mm yttria-stabilized zirconium oxide media until the maximum particle size was less than 0.5 microns, as shown on a Hegman gauge with a 0.5 scale grade indicated at 0-12 microns. The resulting dispersion was pourable.

[0056] Example 6 - Dispersion of a 2:1 mixture of sodium lignin sulfonate:calcium lignin sulfonate and polyglyceryl-2 dipolyhydroxystearate in caprylic / capric triglyceride

[0057] 30.0 parts by weight of a mixture of sodium lignin sulfonate: calcium lignin sulfonate (Marasperse C-21, Borregaard LignoTech) in an approximate ratio of 2:1 was mixed with 13.5 parts by weight of polyglyceryl-2 dipolyhydroxystearate and 56.5 parts by weight of caprylic / capric triglyceride. The mixture was stirred until homogeneous, transferred to a horizontal media mill, and pulverized using 0.3 mm yttria-stabilized zirconium oxide media until the maximum particle size was less than 0.5 microns, as indicated on a Hegman gauge with a 0.5 scale graduation indicating 0–12 microns. The resulting dispersion was pourable.

[0058] Example 7 - Dispersion of Potassium Humate and Polyglyceryl-2 Dipolyhydroxystearate in Caprylic / Capric Triglyceride

[0059] 30.0 parts by weight of potassium humate (Borregro HA-2, Borregaard LignoTech) was mixed with 13.5 parts by weight of polyglyceryl-2 dipolyhydroxystearate and 56.5 parts by weight of caprylic / capric triglyceride. The mixture was stirred until homogeneous, transferred to a horizontal media mill, and pulverized using 0.3 mm yttria-stabilized zirconium oxide media until the maximum particle size was less than 0.5 microns, as indicated by a Hegman gauge with a 0.5 scale grade indicated at 0-12 microns. The resulting dispersion was pourable.

[0060] Example 8 - Dispersion of Sodium Lignosulfonate and Cetyl Diglyceryl Tris(trimethylsiloxy)Silylethyl Dimethicone in Caprylic / Capric Triglyceride

[0061] 30.0 parts by weight of sodium lignin sulfonate (VanisperseA, Borregaard LignoTech) was mixed with 13.5 parts by weight of hexadecyl diglyceryl tris(trimethylsiloxy)silylethyl polydimethylsiloxane and 56.5 parts by weight of caprylic / capric triglyceride. The mixture was stirred until homogeneous, transferred to a horizontal media mill, and pulverized using 0.3 mm yttria-stabilized zirconium oxide media until the maximum particle size was less than 0.5 microns, as indicated on a Hegman gauge with a 0.5 scale grade indicated at 0–12 microns. The resulting dispersion was pourable.

[0062] Example 9 (Comparative Example) - Aqueous Slurry of Sodium Lignosulfonate and Alumina

[0063] According to the preparation of sodium lignin sulfonate aqueous solution as described in the U.S. Patent No. 6,500,411, the U.S. Patent No. 6,716,418 and the U.S. Patent Application No. 2010 / 0202985. 30 parts by weight of sodium lignin sulfonate (VanisperseA, Borregaard LignoTech) are added to 70 parts by weight of deionized water. The solution is stirred until the sodium lignin sulfonate is completely dissolved. 60 parts by weight of submicron (D50 measured by static light scattering is 0.42 microns by volume) plate-like alumina (E390, Saint-Gobain) are added to the solution. The resulting slurry is mixed for 30 minutes using a disperser blade. The resulting aqueous slurry is uniform and easy to pour.

[0064] Example 10 - Humectant containing phenolic polymer in the oil phase

[0065] The moisturizer composition was prepared as a water-in-oil emulsion comprising the dispersion of Example 1 in the oil phase. The ingredients of the moisturizing composition were as follows:

[0066]

[0067]

[0068] Using a cold process, the ingredients of the oil phase were combined and mixed until homogeneous, and separately, the ingredients of the water phase were combined and mixed until homogeneous. The two phases were then combined and homogenized using a Ross HSM-100LC1 homogenizer at 5,000 RPM for 4 minutes. The resulting emulsion was stable after aging for 75 days at 50°C and was very water resistant. The presence of lipophilic dispersed phenolic polymer particles in the oil phase produces a moisturizer with HEV blocking and antioxidant properties.

[0069] Example 11 - Moisturizing Sunscreen Containing Phenolic Polymers in the Oil Phase

[0070] The sunscreen composition was prepared as a water-in-oil emulsion comprising the dispersion of Example 1 in an oil phase. The ingredients of the sunscreen composition are as follows:

[0071]

[0072]

[0073] Using a cold process, the ingredients of the oil phase were combined and mixed until homogeneous, and separately, the ingredients of the water phase were combined and mixed until homogeneous. The two phases were then combined and homogenized using a Ross HSM-100LC1 homogenizer at 5,000 RPM for 4 minutes. The resulting emulsion was stable after aging for 75 days at 50°C and was very water resistant. The presence of lipophilic dispersed phenolic polymer particles produces a moisturizing sunscreen with HEV blocking and antioxidant properties.

[0074] Example 12 - Concealer Containing Phenolic Polymer in Oil Phase (Prospective)

[0075] A concealer composition was prepared as an anhydrous composition comprising the dispersion of Example 1. The ingredients of the concealer were as follows:

[0076]

[0077] Phase A was combined and mixed under high shear conditions. Phase B was added to Phase A and the mixture was heated to 85°C under high shear conditions. Phase C was dispersed into the mixture under high shear conditions while maintaining the temperature at 85°C. The batch was then cooled under high shear mixing. Once the mixture was cooled to below 65°C, Phase D and Phase E were gradually added to the mixture under high shear mixing. The batch was allowed to continue cooling until the temperature reached 60°C. The batch was then dispensed into final packaging. The presence of lipophilic dispersed phenolic polymer particles produces a concealer with HEV blocking and antioxidant properties.

[0078] Example 13 - HEV blocking studies

[0079] The HEV blocking of the dispersion of Example 1 and the comparative aqueous slurry of Example 9 were compared. HEV blocking was measured using a diffuse transmission method similar to the methods described in 21 CFR §201.327 (Over-the-counter sunscreen drug products; Labeling according to effectiveness testing requirements) and ISO 24443 (Determination of UVA photoprotection of sunscreens in vitro).

[0080] 1.3mg / cm 2 The dispersion of Example 1 was applied to the surface of an optical grade polymethyl methacrylate (PMMA) substrate having a rough three-dimensional surface topography (LabSphere HelioPlate HD6). The dispersion was applied uniformly to the substrate surface to correspond to 0.39 mg / cm 2 The aqueous slurry of Example 9 was applied to the substrate in a similar manner to correspond to a delivery dose of 0.39 mg / cm 2 The delivered dose of phenolic polymer.

[0081] The samples were visually inspected and both samples showed a characteristic brown color associated with light absorption in the HEV region. The samples were then left at room temperature for 1 hour. The absorbance of both samples and a control blank optical grade PMMA substrate was measured at a HEV wavelength of 450nm using a LabSphere UV-2000S spectrophotometer. The net absorbance value was determined by subtracting the absorbance of the control blank substrate from the sample absorbance measured on the substrate.

[0082] The monochromatic protection factor (MPF) at 450 nm was determined according to the method in Bleasel, MD et al., "In vitro evaluation of sun protection factors of sunscreen agents using a novel UV spectrophotometric technique", International Journal of Cosmetic Science, Vol. 30, No. 4, pp. 259-270 (2008). The MPF can be expressed by the following equation 2:

[0083] Equation 2:

[0084] where A(λ) is the net absorbance of the sample at wavelength λ.

[0085] The results are shown in the following table:

[0086] sample Net absorbance (450nm) MPF(450nm) Dispersion of Example 1 1.224 16.77 Aqueous slurry of Example 9 0.711 5.14

[0087] The dispersion of Example 1 exhibited greater net absorbance and greater MPF than the aqueous slurry of Example 9. These results indicate that the phenolic polymer dispersed in the oil phase has superior HEV blocking compared to the aqueous slurry of the phenolic polymer.

[0088] Example 14 - Water resistance study

[0089] The water resistance of the dispersion of Example 1 was compared with the comparative aqueous slurry of Example 9. Water resistance was measured using an 80-minute water immersion sequence in accordance with COLIPA 2005 (Cosmetics Europe, "Guidelines for evaluating sun product water resistance," available online at www.cosmeticseurope.eu / files / 7914 / 6407 / 7400 / Guidelines_for_Evaluating_Sun_Product_Water_Resistance_-_2005.pdf, page 15 (2005)), but performed in vitro.

[0090] A 22 cm high x 16 cm diameter stainless steel container was filled with deionized water and maintained at a temperature between 30–33°C. The container was stirred at 350 RPM using a 5 cm diameter flat blade impeller throughout the test. The dispersion sample of Example 1 and the comparative aqueous slurry sample of Example 9 were suspended in the container near the container wall with the applied sample facing the impeller. After 80 minutes of soaking, the sample was removed from the container and dried for 1 hour. The net absorbance and monochromatic protection factor (MPF) were measured as described in Example 13. The results are shown in the following table:

[0091] Measurement Dispersion of Example 1 Aqueous slurry of Example 9 Net absorbance before immersion in water (450nm) 1.224 0.711 MPF before immersion in water (450nm) 16.77 5.14 Net absorbance after immersion in water (450nm) 1.167 0.012 MPF after immersion in water (450nm) 14.70 1.03 Maintain MPF% 88 20

[0092] The dispersion of Example 1 was able to maintain 95% of the net absorbance (450 nm) and maintain 88% of the initial MPF (450 nm) value. These results indicate that the dispersion of Example 1 is very water resistant. Visual inspection showed that the aqueous slurry of Example 9 lost most of the characteristic brown color associated with HEV decay after immersion for 120 seconds. In addition, the aqueous slurry of Example 9 did not meet the requirements for classification as very water resistant. These results indicate that the lipophilic dispersed phenolic polymer particles in the oil phase have excellent water resistance compared to the aqueous slurry of the phenolic polymer.

[0093] Example 15 - Free Radical Quenching and Photostability Studies

[0094] The dispersion of Example 1 was studied for free radical quenching and photostability. Photostability was determined according to the modified DPPH photostability test (see definition section). Free radical quenching was determined according to the free radical quenching assay (see definition section). Titanium dioxide was used as a comparative substance because it is known to be essentially non-photostable (photocatalytic) and to generate large amounts of photoinduced free radicals when exposed to UV radiation.

[0095] Five light stability tests were conducted using different amounts of the dispersion of Example 1 and reference titanium dioxide. The results are shown in the following table:

[0096] test Example 1 Phenolic polymer % in dispersion <![CDATA[TiO2%]]> ΔE Standard Deviation 1 0.115 0 0.65 0.441 2 0.0575 0.0575 3.91 0.166 3 0.115 0.115 1.01 0.082 4 0 0.115 18.84 1.104 5 0 0.0575 14.85 0.398

[0097] The results of Test 1 show that the dispersion of Example 1 is super photostable. In contrast, an equivalent amount of reference titanium dioxide (Test 4) is not super photostable and produces 29 times the concentration of free radicals. Compositions containing equal amounts of the dispersion of Example 1 and titanium dioxide (Tests 2 and 3) are super photostable, indicating that the dispersion of Example 1 actively quenches 73.7% to 94.7% of the free radicals generated by the highly photoactive reference material. The dispersion of Example 1 passed the free radical quenching test at both weight percentages.

[0098] The results showed that the lipophilic dispersed phenolic polymer particles in the oil phase were super photostable and passed the free radical quenching test. The free radical quenching ability is an indicator of the antioxidant properties of the lipophilic phenolic polymer. The results also showed that the lipophilic phenolic polymer particles can be combined with highly photoactive substances to produce super photostable compositions that protect users from UV-generated free radicals.

[0099] References

[0100] 1. U.S. Patent No. 6,500,411.

[0101] 2. U.S. Patent No. 6,716,418.

[0102] 3. U.S. Patent No. 8,309,063.

[0103] 4. U.S. Patent No. 8,445,562.

[0104] 5. U.S. Patent No. 8,911,976.

[0105] 6. U.S. Patent No. 10,035,928.

[0106] 7. U.S. patent application publication number 2007 / 0178057.

[0107] 8. U.S. patent application publication number 2010 / 0202985.

[0108] 9. U.S. patent application publication number 2015 / 0166836.

[0109] 10. U.S. patent application publication number 2018 / 0291210.

[0110] 11. International patent application with publication number WO 2009 / 038477.

[0111] 12. International patent application with publication number WO 2014 / 144746.

[0112] 13. International patent application with publication number WO 2014 / 164418.

[0113] 14. International patent application with publication number WO 2017 / 197530.

[0114] 15. Pan,

[0115] 16. Cosmetics Europe, “Guidelines for evaluating sun product water resistance,” available online at www.cosmeticseurope.eu / files / 7914 / 6407 / 7400 / Guidelines_for_Evaluating_Sun_Product_Water_Resistance_-_2005.pdf, 15 pages (2005).

[0116] 17. Bleasel, MD et al., “In vitro evaluation of sun protection factors of sunscreen agents using a novel UV spectrophotometric technique,” ​​International Journal of Cosmetic Science, vol. 30, no. 4, pp. 259–270 (2008).

[0117] 18. The International Lignin Institute, “About lignin,” available online at www.ili-lignin.com / aboutlignin.php (accessed August 30, 2019).

Claims

1. A dispersion comprising: Phenolic polymer particles, a surfactant on the phenolic polymer particles, and Carrier medium; wherein the dispersion is very water-resistant, The phenolic polymer particles are in a solid state, The phenolic polymer is a water-soluble polymer containing a plurality of OH-substituted phenyl groups. The particle size of the phenolic polymer particles is 0.001-10.0 microns, The amount of the phenolic polymer particles is 0.1-75.0% by weight. The amount of the surfactant is 1.0-100.0% of the mass of the phenolic polymer particles. The phenolic polymer particles include a material selected from the group consisting of lignin, humate, and a combination thereof, The surfactant comprises a material selected from the group consisting of polyglyceryl polyester, polyglyceryl-2 dipolyhydroxystearate, phospholipids, substituted silicone resins having affinity groups, and combinations thereof, and The carrier medium comprises a lipophilic, cosmetically acceptable fluid selected from the group consisting of caprylic / capric triglyceride, coco-caprylate, C12-C15 alkyl benzoate, and combinations thereof.

2. The dispersion according to claim 1, wherein: The phenolic polymer particles include sodium lignin sulfonate particles, The particle size of the sodium lignin sulfonate particles is 0.1-1.0 microns, and The dispersion is pourable.

3. The dispersion of claim 2, wherein the surfactant comprises polyglyceryl-2 dipolyhydroxystearate; The lipophilic cosmetically acceptable fluid comprises caprylic / capric triglyceride; The amount of sodium lignin sulfonate is 1.0-40.0% by weight, and The amount of polyglyceryl-2 dipolyhydroxystearate is 15.0-50.0% by weight.

4. The dispersion according to claim 3, wherein the dispersion is super photostable.

5. The dispersion of claim 3, wherein the dispersion passes a free radical quenching test.

6. A sunscreen composition comprising: The dispersion according to claim 1, and UV radiation protectant.

7. The sunscreen composition according to claim 6, wherein the UV radiation protectant is selected from zinc oxide, titanium dioxide, p-aminobenzoic acid, isooctyl p-dimethylaminobenzoate, phenylbenzimidazole sulfonic acid, cinoxate, dioxybenzone, oxybenzone, homosalate, menthyl anthranilate, octocrylene, octyl methoxycinnamate, octyl salicylate, sulisobenzone, triethanolamine salicylate, avobenzone, ezcid, cerium oxide, domethoxazole trisiloxane, bis-ethylhexyloxyphenol methoxyphenyl triazine, bis-isotriazole and combinations thereof.

8. Use of the dispersion according to claim 1 for preparing a preparation for protecting human skin.

9. Use of the dispersion according to claim 1 for preparing a preparation for treating or preventing oxidative damage to the skin.

10. Use of the dispersion according to claim 1 for preparing a preparation for protecting keratinous materials, The keratinous material is selected from the group consisting of hair, fingernails, toenails and the outer layer of skin.

11. Use of the dispersion according to claim 1 for preparing a preparation for inhibiting lipid peroxidation in the skin.

12. Use of the dispersion according to claim 1 for preparing a preparation for preventing or reducing the appearance of skin wrinkles.

13. Use of the dispersion according to claim 1 for preparing a preparation for preventing loss of skin elasticity.

14. Use of the dispersion according to claim 1 for preparing a preparation for preventing skin thinning.

15. Use of the dispersion according to claim 1 for preparing a preparation for preventing skin pigment darkening.

16. Use of the dispersion according to claim 1 for the preparation of a formulation for attenuating HEV radiation exposure to the skin.

17. Use of the dispersion according to claim 1 for preparing a preparation for quenching free radicals in keratinous materials, The keratinous material comprises hair or skin.

Citation Information

Patent Citations

  • Lignin nanoparticle dispersions and methods for producing and using the same

    US10035928B2

  • Sunscreen compositions including particulate sunscreen actives that exhibit boosting of sun protection factor

    US20100202985A1

  • Lignin nanoparticle dispersions and methods for producing and using the same

    US20150166836A1

  • Coated powders having high photostability

    US20180291210A1

  • Multifunctional particulate additive for personal care and cosmetic compositions, and the process of making the same

    US6500411B2